Pengaruh Etos Kerja, Beban Kerja, dan Disiplin Kerja Terhadap Kinerja Internship Fasilitator Pendamping PT Bank Syariah Tbk MSIB Batch 5 di Jember - Utami, Diandra Weningtyas; Agus Priono; Krishnabudi, N. G; Saleh, Chairul (Study Program of Management Faculty of Economics and Business University of Jember, 2025)
In the increasingly advanced era of globalization, competition in the workforce is becoming more intense, making the quality of human resources (HR) a critical factor in the success of an organization. This also applies to internship programs, where the quality of facilitators plays a key role in competency development. Therefore, improving the performance of facilitators in managing internship programs needs to be taken seriously. One of the factors influencing facilitator performance is work ethic, workload, and work discipline. Hence, this study aims to identify and analyze the significant effects of work ethic, workload, and work discipline on the performance of internship facilitators mentoring at PT Bank Syariah Tbk in Jember. This research uses an explanatory research design. The data type used is quantitative, and the data sources were obtained from interviews, questionnaires, and literature reviews. The sample consists of 30 interns participating in the MSIB Batch 5 internship program at PT Bank Syariah Tbk Jember. This study employs multiple linear regression analysis using IBM SPSS Statistics software. The results of the study partially prove that work ethic has a significant effect on internship performance, workload has a significant effect on internship performance, and work discipline has a significant effect on internship performance.